Urban Ecosystem services on the local level: Urban green spaces as providers - Breuste Jürgen; Schnellinger Johanna; Qureshi Salman; Faggi Anna (Ekológia (Bratislava), 2013)
Breuste J., Schnellinger J., Qureshi S., Faggi A.: Urban ecosystem services on the local level: Urban green spaces as providers. Ekologia (Bratislava), Vol. 32, No. 3, p. 209-304, 2013. Ecosystem services are provided at different spatial and service/functional scales. The local level is the basic unit for ecosystem services, especially when it comes to the human dimension of urban landscapes. These services are provided by green elements (patches) or basic complex ecosystems (green areas) which differ from their neighbourhoods through their structures and functions. This study reviews the generally available knowledge on urban green functions and services at the site level and explains them by using own studies in five different cities in three different continents related to distinct ecosystem services. This allows the development of a methodology to evaluate and compare ecosystem services at the site level. The methodology is based at two levels, patch and green space, and includes the relationship with the surrounding green and built-up space. Different urban green space types are characterized by their internal structures of vegetation, size, shape and location in relation to at least a semi-quantitative scaling of their urban ecosystem services. The evaluated urban green spaces are public urban green spaces. The urban ecosystem services assessed include climate regulation, biodiversity, nature experience, recreation and health. The actual urban challenges, such as land use change, adaptation to climate change, demographic change and urban cultural diversity, demand a systematic and very concrete monitoring of urban ecosystem services at the site level.